Pengembangan Awal University Academic Self-Efficacy Scale (UASES) pada Mahasiswa Indonesia: Studi Pilot - An Nisa Dwi Syah Putri; Nadya Odetta Siahaan; Naela Uktuvia Rangkuti; Syifa Nazla Silmi; Vita Aulia Rahmah; Dina Nazriani (Universitas Palangka Raya, 2026)
Academic self-efficacy refers to individuals’ belief in their ability to complete academic tasks and achieve academic goals. This study aimed to develop and evaluate the initial content validity and reliability of the University Academic Self-Efficacy Scale (UASES) among undergraduate students in Indonesia. A total of 116 active undergraduate students aged 18–25 years participated in this study using accidental sampling. Content validity was analyzed using Aiken’s V coefficient, while reliability was assessed using Cronbach’s Alpha with the assistance of JASP software. The results indicated that the UASES demonstrated adequate dimension-level content validity across four dimensions, namely self-engagement, self-oriented decision-making, others-oriented problem-solving, and interpersonal climate, with Aiken’s V values ranging from 0.583 to 0.917 and a mean of 0.737. The overall scale reliability showed good internal consistency, with a Cronbach’s Alpha value of 0.855. Based on score categorization, 92% of participants were in the moderate category and 8% were in the high category. These findings suggest that the UASES provides promising initial psychometric evidence as a measure of academic self-efficacy among Indonesian university students. Nevertheless, further research is needed to review items requiring revision, examine construct validity, and confirm the factor structure of the instrument using larger and more diverse samples.